The Treatment of Superior Responsibility in Colombia: Interpreting the Agreement Between the Colombian Government and the FARC † (2019)
The Colombian Constitutional and Supreme Court’s interpretation of superior responsibility as cases of commission by omission and indirect perpetration excludes most military superiors’ omissions of their duties to prevent, repress and submit subordinates’ international crimes to the competent authorities. Nevertheless, the notion of complicity by omission, as a form of accessorial liability, and the crime of abetting could cover this gap with regard to omissions carried out by military superiors with dolus. Furthermore, although Colombian criminal law does not provide for negligent military superiors’ omissions, the Colombian Armed Forces Operational law attaches disciplinary responsibility to military superiors’ omissions, which are carried out with gross negligence. Moreover, the Peace Agreement of 24 November 2016 between the Colombian Government and the Revolutionary Armed Forces of Colombia – Popular Army (‘the FARC’), explicitly provides for criminal liability for gross negligent omissions of Colombian Security Forces superiors and FARC superiors with regard to subordinates’ international crimes related to the armed conflict. Further, the provisions of the Agreement on superior responsibility of Colombian Security Forces superiors have been subsequently incorporated into the Colombian Constitution by the 4 April 2017 Legislative Act 01/2017 and the provisions relating to FARC superiors were incorporated into Colombian law through the 30 November 2017 Law on the Special Jurisdiction for Peace. Although this approach was upheld by the 24 November 2017 Colombian Constitutional Court (‘CCC’) judgment C-674/2017 and the CCC’s 16 August 2018 public statement, which declared, respectively, the constitutionality of Legislative Act 01/2017 and the Law on the Special Jurisdiction for Peace, this position has come at a high prize because not only have all references to international law been eliminated from the definition of superior responsibility for Colombian Security Forces superiors (they have only been kept in relation to FARC superiors), but several additional requirements have also been added to the definition. The result significantly restricts the scope of application. Last but not least, the notion of superior responsibility for civilian superiors is not yet applicable in Colombia due to the absence of an explicit reference to it under Colombian law and the Colombian Constitutional Court’s ‘distinctive approach’ doctrine. © 2018, Springer Nature B.V.